(untitled) (Journal of Environmental Science Studies, 2018)
In view of the up-scaling energy crises worldwide, efforts have been focusing on reducing energy consumption and replacing fossil fuels usage with renewable energy sources. Thailand is one of the developing countries that have been facing an increase in energy demand associated to its economic expansion. The development in the educational sector is one of the sectors causing an increasing energy demand. Purpose: This study aims to quantify energy usage and understand its environmental impacts in one of the educational facilities in Thailand in order to identify energy saving opportunities and improvement options related to energy consumption in this sector. Materials and Methods: The investigation included a historical energy analysis for energy utilization of the facility, an onsite energy audit and an environmental impacts assessment. A number of potential energy saving opportunities was identified; related cost savings and CO reduction were calculated. Additionally, the 2 environmental impacts of energy utilization were simulated using the life cycle assessment technique. Special attention was given to potential impacts on global warming due to its direct association to fossil fuels combustion. Results and discussion: the pattern of energy utilization was identified and it clarified that the major contributor to energy utilization was energy consumption practices by students and staff of the faculty. Consequently, awareness raising of energy saving opportunities and people involvement was the major area of improvement. Results show that increasing people involvement in energy saving practices could lead to a cost saving of 46,000-120,000 USD/Year with low cost investment and a 100-240 ton CO reduction. Other potential savings 2 were using motion sensors which save 30-40% of energy costs in offices and utilizing renewable solar energy as a source for electricity. This will save 13,300-33,300 USD/Year with a 7.5 years payback and 35-50 years lifetime. When assessing the associated environmental impacts to electricity production, five main categories were found to be impacted: fossil fuels depletion, respiratory inorganics formation potential, global worming potential, acidification potential and eutrophication potential. The application of the suggested energy saving opportunities will reduce the electricity consumption, lower generated air emissions from fossil fuels combustion, consequently minimize all associated impacts specially global worming potential. In Conclusion: assessing energy utilization of educational facilities is essential to reduce energy demand in an up-scaling economy. Energy analysis and onsite energy audits are efficient methods for recognizing energy utilization patterns and identifying energy saving opportunities. The implemented investigation in this study can be applied in different educational facilities.